2023
DOI: 10.1002/app.54406
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid loaded nanospheres/biodegradable PVA‐sodium alginate hydrogel for wound healing application

Kimia Kabirian Kholghi,
Pari Tamri,
Rasool Haddadi
et al.

Abstract: In the present study, a novel polyvinyl alcohol‐sodium alginate hydrogel was prepared using ellagic acid loaded nanospheres in its structure. Ellagic acid was loaded into polymeric nanospheres using a double‐emulsion solvent evaporation technique. Obtained nanospheres were dispersed in a polyvinyl alcohol‐sodium alginate hydrogel, prepared using freeze–thaw method followed by freeze‐drying. Ellagic acid loaded nanospheres and the final hydrogel preparation were characterized using scanning electron microscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Thereby, it is important for the cytotoxicity each material to be studied. Mohammadinejad et al confirmed the anticancer activity of ellagic acid [ 39 ], while Kholghi et al [ 40 ] studied the cytotoxicity of PVA-sodium alginate hydrogels containing different concentrations of EA. Their results indicated that EA nanosphere-containing hydrogels did not have any cytotoxic effect, suggesting that toxicity depended on the concentration of ellagic acid released from the material.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, it is important for the cytotoxicity each material to be studied. Mohammadinejad et al confirmed the anticancer activity of ellagic acid [ 39 ], while Kholghi et al [ 40 ] studied the cytotoxicity of PVA-sodium alginate hydrogels containing different concentrations of EA. Their results indicated that EA nanosphere-containing hydrogels did not have any cytotoxic effect, suggesting that toxicity depended on the concentration of ellagic acid released from the material.…”
Section: Discussionmentioning
confidence: 99%